A study of affecting the recovery of Chinese patients with Bell palsy. Issue 4 (January 2019) - Zhang, Hongbo; Du, Haixia; Qian, Mingjing; Wang, Yu; Zhou, Shenghua; Chen, Jing; Wan, Haitong; Yang, Jiehong
Abstract : Abstract: We explored the risk factors for preventing recovery of Bell palsy (BP) in Chinese inpatients. Five hundred thirteen patients were included. The two end-points of assessment were the discharge and final follow-up results. Relationship between discharge and baseline: long patients delay (unhealed 4.03 ± 1.16 d vs improved 2.24 ± 1.0 d, P < .001), combined diseases (yes 77.06% vs no 86.71%, P = .01), and early use of acupuncture (yes 47.46% vs no 97.62%, P < .001) were bad factors. Therapeutic factors and discharge: only use of steroids was a positive factor (yes 92.54% vs no 57.30%, P < .001). Binary logistic regression found that early use of steroids was a favorable factor ( P = .001), while early use of acupuncture ( P < .001) and long patient delay ( P < .001) were adverse factors. Subgroups analysis showed early use of steroids plus antivirals (steroids + antivirals vs antivirals + mecobalamin, P < .001) and early use of steroids plus mecobalamin were good choices (steroids + antivirals vs steroids + mecobalamin, P = .745), while early use of antivirals plus mecobalamin was a bad choice (vs other 2 groups, P < .001). Effect of drug dose and treatment course on discharge: long time use of steroids didn't mean good efficacy (unhealed 10.80 ± 1.53 d vs improved 10.38 ± 1.21 d, P = .026). Final follow-up results: improved patients were better than that of unhealed at discharge ( P < .001). Risk factors of discharge included long patient delay, combined diseases, and early use of acupuncture. Steroids plus antivirals or steroids plus mecobalamin were good choices for treatment. Long time use of steroids didn't mean good effect. Improved patients at discharge had better results finally.